An AC voltage regulator with high-power-factor, and control using a FPGA device - Dantas, Fausto Donizeti; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
This paper presents the analysis, design, simulation, and experimental results for a high frequency high Power-Factor (PF) AC (Alternate Current) voltage regulator, using a Sepic converter as power stage. The control technique employed to impose a sinusoidal input current waveform, with low Total Harmonic Distortion (THD), is the sinusoidal variable hysteresis control. The control technique was implemented in a FPGA (Field Programmable Gate Array) device, using a Hardware Description Language (VHDL). Through the use of the proposed control technique, the AC voltage regulator performs active power-factor correction, and low THD in the input current, for linear and non-linear loads, satisfying the requirements of the EEC61000-3-2 standards. Experimental results from an example prototype, designed for 300W of nominal output power, 50kHz (switching frequency), and 127Vrms of nominal input and output voltages, are presented in order to validate the proposed AC regulator. © 2005 IEEE.
Keywords: AC voltage regulator; FPGA device; High Power-Factor; VHDL language; FPGA devices; Electric circuit breakers; Electric converters; Electric potential; Field programmable gate arrays; Harmonic analysis; Waveform analysis; Voltage control